A rutting-based optimum maintenance decision strategy of hot in-place recycling in semi-rigid base asphalt pavement - Pan, Yuanyuan; Liu, Guoqiang; Tang, Dong; Han, Dongdong; Li, Xuanguo; Zhao, Yongli (Journal of cleaner production, 2021)
Hot in-place recycling (HIR), 100% recycling reclaimed asphalt pavement (RAP) directly on a construction site, has been widely used as a sustainable maintenance treatment. Since the RAP provides aged asphalt and dense skeleton structure, the HIR is beneficial to restoring pavement rutting resistance. With ever-increasing maintenance requirements whereas limited maintenance budgets, a rutting-based optimum maintenance decision strategy of hot in-place recycling in semi-rigid base asphalt pavement is proposed. It contains the selection of maintenance sections using the peak cutting method in a multi-objective optimization model and the determination of maintenance timing by the arching depth rather than long-term pavement performance. To verify, a case study based on a HIR project of an existing expressway in Jiangsu Province in China is conducted. Results confirms the economy and effectiveness of the peak cutting method in selecting maintenance sections by comparison with the traditional empirical method. With the finite element simulation, the arching depth is proved as the dominant factor of the temperature of asphalt mixtures in milling process. Based on the confidence level of milling temperature, maintenance timing related threshold of arching depth are recommended. Consequently, the proposed maintenance decision strategy could provide the highway management department with guidance in selecting maintenance sections and determining maintenance timing at a critical pre-requisite of saving maintenance funds and restoring pavement serviceability.